MENINGKATKAN HASIL BELAJAR MELALUI MEDIA PEMBELAJARAN BERBASIS FILM DI KELAS X PADA MATA PELAJARAN SKI DI MA URWATUL WUTSQO - Khurum Maqsuroh; Sufinatin Aisida; Nurul Ayu Fadilah; Nur Tamimah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to improve student learning outcomes in the subject of Islamic Cultural History (SKI) in class X MA Urwatul Wutsqo through the application of film-based learning media. The background of this problem is the low student learning outcomes caused by learning methods that tend to be monotonous and the lack of innovative media. This research uses a qualitative approach with a type of classroom action research (PTK) consisting of two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The subjects of this research were MA Urwatul Wutsqo grade X students. Data were collected through observation, interviews, tests, and documentation. The results showed a significant increase in student learning outcomes from cycle I to cycle II. In cycle I, the average score of students' learning outcomes reached 74, and in cycle II it increased to 81. In addition, students' activities and enthusiasm in participating in learning also increased drastically after the use of film media. Thus, it can be concluded that the use of film-based learning media is effective in improving student learning outcomes and activeness in SKI subjects in class X MA Urwatul Wutsqo.